KEANEKARAGAMAN JENIS BURUNG DI SEKITAR MATA AIR BRON DESA WAREMBUNGAN KABUPATEN MINAHASA - Muhammad Rezah M Ishak; Johny S. Tasirin; Wawan Nurmawan (COCOS, 2018)
ABSTRACTBirds are one of the biological wealth possessed by Indonesia. The presence of feed, nesting sites and stops is a factor that influences bird species' wealth at the local level. Birds are found in almost every place and have an important position as one of Indonesia's animal wealth. Birds also have a close connection with human life since time immemorial. This study aims to inventory and analyze the diversity of bird species and their abundance around the eyes of Bron water, Warembungan Village, Minahasa Regency. The study was conducted from August to September 2016 around the eyes of Bron's water, Warembungan Village, Minahasa Regency. Data retrieval is done by the IPA-Count method. The results of observations were found 49 species of birds from 26 families, with the Shannon-Wiener index value 2.44 as an indication of the diversity of species of birds around the Bron spring. Keywords : Birds, Bird species diversity, Around the Bron spring